Intermedialność adaptacji, adaptacja intermedialności. Gry z dyskursem hiphopowym w Innych ludziach (Doroty Masłowskiej i Aleksandry Terpińskiej) - Birkholc, Robert (Przestrzenie Teorii, 2025)
This article explores the concept of intermediality in the context of contemporary film adaptations. As the author argues, this category not only highlights the necessity of considering multiple media in the analysis of adaptation processes, but also serves as an effective tool for describing specific contemporary narrative strategies. The study focuses on Dorota Masłowska’s novel Other People (Inni ludzie), and its adaptation by Aleksandra Terpińska. The author examines how Masłowska and Terpińska employ literary and cinematic means of expression to create intermedial references to the discourse of hiphop. The analysis aims not only to demonstrate the dynamic interaction between different media forms, but also to show the potential of intermedial references as a tool for social critique. According to the author, Other People is not an example of remediation in the strict sense, but rather of reflective intermediality, which encourages to examine the referenced discourse from a critical distance.